Unfilterable Beer Haze Part I: The Investigation of an India Pale Ale Haze. (10th January 2022) - Huismann, Margaux; Gormley, Fraser; Dzait, Dzeti; Speers, R. Alex; L. Maskell, Dawn
Abstract: The nature of undesirable and unfilterable haze particles observed by craft breweries remains nebulous and presents a challenge when the aim is the production of bright beer. A commercial beer was studied in which the brewery had sporadically encountered unfilterable haze. In this study, it was hypothesized that unfilterable haze particles were formed due to increased concentrations of proteins, polyphenols, and/or beta-glucans. Samples of a high haze and low haze India Pale Ale were degassed and digested with enzymes amyloglucosidase, pepsin, and UltraFlo Max (Novozymes TM ). Additionally, the protein, polyphenol, and beta-glucan content of each sample was measured. When comparing protein, polyphenol, and beta-glucan concentrations substantial differences between high haze and low haze protein concentrations were observed. Due to the unfilterable nature of these hazes, combined with experimental findings, it was hypothesized that yeast cell-wall proteins were responsible for this haze. Understanding of the source of these hazes offers brewers the opportunity to mitigate against their formation by adjusting brewing practices.